Successful cardiopulmonary resuscitation in an adult horse following cardiovascular collapse on recovery from general anaesthesia in the Trendelenburg position. (29th March 2021) - Duggan, M.; Schofield, W.; Vermedal, H.
Summary: Equine anaesthesia is associated with a high risk of perioperative morbidity and mortality, particularly in the recovery period. Cardiovascular collapse and cardiopulmonary arrest (CPA) have been reported to account for one‐third of anaesthesia‐related perioperative deaths in the horse. This case report describes the successful cardiopulmonary resuscitation of a healthy adult Thoroughbred mare that developed cardiovascular collapse and subsequent CPA following positioning in the recovery box after general anaesthesia in the Trendelenburg position. Cardiopulmonary resuscitation (CPR) was instigated and included thoracic compressions, intermittent positive pressure ventilation and adrenaline administered via the intravenous and intra‐tracheal routes. Return of spontaneous circulation (ROSC) was detected 5 min and 50 s after the start of CPR. A stable stance was achieved approximately 100 min after ROSC. The mare was discharged from the hospital 3 days later with no known complications. To the authors' knowledge, this is the first case report documenting CPA following general anaesthesia in the Trendelenburg position in a horse, with subsequent successful CPR. The precise cause of the CPA is unknown but a number of plausible hypothesis are discussed including hypoventilation and a Bezold‐Jarisch reflex.